2022
DOI: 10.3390/gels8090561
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of In Situ Gelling Mucoadhesive Eye Drops Containing Dexamethasone

Abstract: Poor bioavailability of eye drops is a well-known issue, which can be improved by increasing the residence time on the eye surface and the penetration of the active pharmaceutical ingredient (API). This study aims to formulate in situ gelling mucoadhesive ophthalmic preparations. To increase the residence time, the formulations were based on a thermosensitive polymer (Poloxamer 407 (P407)) and were combined with two types of mucoadhesive polymers. Dexamethasone (DXM) was solubilized by complexation with cyclod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…An increase in the concentration of Pluronic F-127 and Pluronic F-68 led to a decrease in the gelling time. The higher gelation time results in the decrease in the residence time, whereas a gelation time of less than 2 min disturbs the distribution of the gel in the nasal cavity . The lag time of gelation was analyzed, which showed that the HJ7DG (in situ gel of the optimized formulation HJ7D in the HJ3G gelling system) formulation possessed the shortest lag time in between 3 and 4 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the concentration of Pluronic F-127 and Pluronic F-68 led to a decrease in the gelling time. The higher gelation time results in the decrease in the residence time, whereas a gelation time of less than 2 min disturbs the distribution of the gel in the nasal cavity . The lag time of gelation was analyzed, which showed that the HJ7DG (in situ gel of the optimized formulation HJ7D in the HJ3G gelling system) formulation possessed the shortest lag time in between 3 and 4 min.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining fluoxetine concentration 332.35 ± 0.35 μg/mL was absorbed in the olfactory region of the brain. In the case of fluoxetine-loaded cubosomal in situ gel, it displayed a sustained release profile for 24 The results of the biodistribution study proposed that both the cubosomal formulations presented the improvement in the brain targeting in contrast to the drug solution (p value <0.001) with an enhanced nasal retention time for the drug to target the brain region. Fluoxetine drug solution revealed lower nasal retention time due to nasal drainage with a C max (97.92 ± 0.35 μg/mL) that was lower than that of formulation HJ7D.…”
Section: Ex Vivo Permeation Study Of In Situmentioning
confidence: 99%
“…Viscosity, pH, and drug content were assessed at 1, 2, and 3 months to confirm the stability of the optimized formulations. [29]…”
Section: In Vivo Pharmacokinetics Studiesmentioning
confidence: 99%
“…Based on all of the above, designing new drug delivery systems that can deliver the appropriate therapeutic concentrations to target tissues and maintain them without or with minimal side effects is the main focus of current research in the field of ophthalmic preparations [ 42 , 43 ].…”
Section: Ocular Anatomy and Physiologymentioning
confidence: 99%